(untitled) (Revista de Ciências Agroveterinárias, 2017)
Seed germination involves complex physiological and biochemical mechanisms. The cultivation of amaranth, of great food importance, lacks information about this process. The aim of this study was to evaluate the effect of temperature, light and different substrates on the germination of amaranth seeds. The experimental design was entirely randomized in a trifactorial scheme, with two temperatures, two conditions of light and four substrates, with four repetitions of 100 seeds each. The percentage of seed germination was evaluated until 24 days of implementation and the cumulative germination at 07, 14 and 24 days. The germination began on the fourth day for the substrate between sand and for the other substrates it began on the eleventh day, stabilizing in the fourteenth day. There was triple significant interaction among temperature, light condition and substrate factors used on the germination test. The best condition for amaranth seed germination is at a 25 ºC temperature, in the absence of light and on paper roll substrate, with 87% of germination. These conditions can be used in germination tests for seed lots, to test its quality.